Strategi Kuliah Sambil Bekerja Oleh Mahasiswa (Studi Kasus: Mahasiswa Bekerja di Universitas Negeri Padang) - Arif Rahman Hakim; Mira Hasti Hasmira (Universitas Negeri Padang, 2022)
This research is motivated by the number of students who study while working but can finish their studies on time, based on this, this study aims to determine the strategies of students who work in completing their studies. The purpose of this study is in line with the analytical theory for the case of